DEVELOPMENT PERSONALITY/SOCIAL COMPETENCY OF SECONDARY HIGH SCHOOL STUDENTS TROUGH A COMPREHENSIVE GUIDANCE AND COUNSELING PROGRAM - Sutoyo, Anwar; Supriyanto, Agus (JURNAL FOKUS KONSELING, 2015)
AbstractÂ The goal this research is to find the effectiveness of model guidance and counseling comprehensive program to develop the personality/ social competency of secondary high school students.This research uses method one group pretest and posttest design. In data collecting technique, this research was directly done through interview, documentation and assessment scale.The conclusions of the research are, The model of guidance and counseling comprehensive program that developed is effective to evolving the personality/ social competency of secondary high school students. Therefore it, counselor need to have leadership ability, create an collaboration atmospherebetweenstakeholders, and tecnology information mastered.Â Keywords: Comprehensive Program; Personality/ Social CompetencyÂ